(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the role and importance of corporate profit tax in the formation of the state budget. The share of tax revenues in state budget revenues, its impact on economic stability, and the development directions of tax policy are highlighted.